ANALISA KEGAGALAN SAMBUNGAN LAS BAJA PADUAN RENDAH (BS-1501-224 Gr 490 BLT 45) - Mochammad Sochib; Budi Astoro (Wahana Teknik, 2012)
Before the manufacture of pressure vessel welding process performed on the test material in which the test material is then carried out the testing process from the mechanical (tensile tests, comparisons, test the hardness and toughness test) of the test results will be obtained from the value of each test and if the value of the produced in accordance with the implied then for the next process can be used for the same job and if the contrary should be tested again with the same procedure from previous work.Testing performed to analyze the causes of failure in welded joints of low alloy steel material (BS 1501-224 Gr 490 BLT 45). Used method of impact testing where the test material will be taken on the position of weld material, fusion and fusion line + line 2mm with test temperature 45Â° C.The first test results are known the value obtained does not meet / achieve the implied value of the standard, but after re-commissioning and testing (re-test) by the same process as before it can be seen where the test results have met both the value of the implied value for the results of testing welded joints of low alloy steel material (BS 1501-224 Gr 490 BLT 45).Keywords : failure, welded joints